The secret in the old attic - Keene, Carolyn; Stratemeyer Syndicate (New York : Grosset & Dunlap, 1970)
Nancy Drew must use clues in a dead man's letters to find some unpublished musical manuscripts that will save an old man and his granddaughter from financial ruin
A challenge -- The old house -- A lost child -- A shadowy figure -- Bony fingers -- A suspected thief -- No admittance -- Song of the wind -- Black widow -- The strange scent -- A blue bottle -- A night prowler -- Locked in the factory -- An underground escape -- Smoke! -- A secret drawer -- An unpleasant caller -- Watching -- Under the wallpaper -- A mean mix-up -- Clues in verse -- The covered skylight -- Sounds in the night -- The trap -- The plotter nabbed
Carolyn Keene is a Stratemeyer Syndicate pseudonym
Johnson, D. Stratemeyer pseudonyms and series
Accelerated Reader AR
Reading Counts RC
Accelerated Reader
Keywords: Drew, Nancy -- (Fictitious character) -- Juvenile fiction; Women detectives -- Juvenile fiction; Mystery and detective stories; Detective and mystery fiction; Detective and mystery fiction